2020
DOI: 10.1101/2020.06.22.164178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The germline mutational process in rhesus macaque and its implications for phylogenetic dating

Abstract: 32Understanding the rate and pattern of germline mutations is of fundamental importance for 33 understanding evolutionary processes. Here we analyzed 19 parent-offspring trios of rhesus macaques 34 (Macaca mulatta) at high sequencing coverage of ca. 76X per individual, and estimated an average 35 r a t e of 0.73 × 10 −8 de novo mutations per site per generation (95 % CI: 0.65 × 10 −8 -0.81 × 36 10 −8 ). By phasing 50 % of the mutations to parental origins, we found that the mutation rate is 37 positively corre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
(131 reference statements)
4
19
0
Order By: Relevance
“…Pedigree-based studies in humans and nonhuman primates have confirmed the paternal origin of a majority of DNMs, consistent with the hypothesis that the number of mutations increase with the father's age (Bergeron et al, 2020;Jónsson et al, 2017;Lindsay et al, 2019;Rahbari et al, 2016;Venn et al, 2014;Wang et al, 2020). The paternal mutation bias may be a more general feature of mammals, as it is also prevalent in domestic cats (Wang et al, 2021) and mice (Lindsay et al, 2019).…”
Section: Cell Division Bias and The Paternal Age Effectsupporting
confidence: 68%
See 1 more Smart Citation
“…Pedigree-based studies in humans and nonhuman primates have confirmed the paternal origin of a majority of DNMs, consistent with the hypothesis that the number of mutations increase with the father's age (Bergeron et al, 2020;Jónsson et al, 2017;Lindsay et al, 2019;Rahbari et al, 2016;Venn et al, 2014;Wang et al, 2020). The paternal mutation bias may be a more general feature of mammals, as it is also prevalent in domestic cats (Wang et al, 2021) and mice (Lindsay et al, 2019).…”
Section: Cell Division Bias and The Paternal Age Effectsupporting
confidence: 68%
“…Despite the fact that spermatogonial stem cells are characterized by highly efficient DNA repair and one of the lowest spontaneous mutation rates in the human body (Aitken et al, 2020), this idea has dominated the mutation rate literature for years. Pedigree‐based studies in humans and nonhuman primates have confirmed the paternal origin of a majority of DNMs, consistent with the hypothesis that the number of mutations increase with the father's age (Bergeron et al, 2020; Jónsson et al, 2017; Lindsay et al, 2019; Rahbari et al, 2016; Venn et al, 2014; Wang et al, 2020). The paternal mutation bias may be a more general feature of mammals, as it is also prevalent in domestic cats (Wang et al, 2021) and mice (Lindsay et al, 2019).…”
Section: The Promise Of the De Novo Mutation Rate For Molecular Ecologysupporting
confidence: 66%
“…The spectrum of mutations in the cat was remarkably similar to those found in most primates, with a preponderance of C>T and A>G transitions (Kong et al 2012;Venn et al 2014;Thomas et al 2018;Besenbacher et al 2019;Bergeron et al 2020;Wang et al 2020;Wu et al 2020;see Campbell et al 2020 for an exception in the mouse lemur). We showed that differences in the mutation spectrum between the cat and the human can in large part be explained by differences in age according to a model of reproductive longevity.…”
Section: Discussionmentioning
confidence: 56%
“…The analysis pipeline and scripts are available via Github [ 69 ] and Zenodo [ 70 ]. Other supporting data are available via the GigaScience database GigaDB [ 74 ].…”
Section: Data Availabilitymentioning
confidence: 99%